Fostering Family–School and Community–School Partnerships in Inclusive Schools: Using Practice as a Guide. (September 2015) - Haines, Shana J.; Gross, Judith M. S.; Blue-Banning, Martha; Francis, Grace L.; Turnbull, Ann P.
Partnerships between school staff, families, and community members are vital for ensuring the success of all students in inclusive schools. This article reports the results of a synthesis of two original studies: one study that examined the perspectives of family members and another study that examined the perspectives of community partners in developing partnerships with school staff at six inclusive knowledge development sites located in five geographic regions within the United States. The current synthesis study analyzes the original studies' overlapping themes to inform concentrated efforts aimed at strengthening family and community partnerships in inclusive schools. Themes of this synthesis study include positive, inviting, and inclusive school culture; strong administrative leadership driven by a clear vision of inclusion; attributes of trusting partnerships; and opportunities for reciprocal partnerships and involvement. Implications for practice and research are discussed.